فاعلية ممارسة النشاط الترويحي الرياضي في تحقيق الصحة النفسية لدى متقاعدي الجيش الوطني الشعبي ( 55 - 40 سنة) - بوزغادة, ناصر (Institut d'Éducation Physique et Sportive - Mostaganem 2023/2024, 2024)
عنوان الدراسة : أهمية ممارسة النشاط الترويحي الرياضي في تحقيق الصحة النفسية لدى متقاعدي الجيش الوطني الشعبي 40-55 سنة. هدفت الدراسة الحالية إلى معرفة أهمية ممارسة النشاط الترويحي الرياضي في تحقيق الصحة النفسية لدى متقاعدي الجيش الوطني الشعبي سن 40 ـ 55 سنة . مستعينا بعينة قدرت ب 50 أستاذ موزعين إلى مجموعتين إحداهما 25 متقاعد ممارسين للنشاط الرياضي الترويحي و العينة الثانية 25 متقاعد أستاذ لا يزاولون أي نشاط رياضي و تم استخدام المنهج الوصفي مستعينا بمقياس الصحة النفسية . وعليه افترض الطالب ـأنه يتميز متقاعدي الجيش الوطني الشعبي سن 40 ـ 55 سنة الممارسين للأنشطة الترويحية والرياضية بمستوى صحة نفسية مرتفع مقارنة مع أقرانهم غير الممارسين للأنشطة الترويحية الرياضية بمستوى صحة نفسية متوسط و الفرضية الثانية توجد فروق ذات دلالة إحصائية عند مستوى الدلالة(0.05≥α) لدى متقاعدي الجيش الوطني الشعبي سن 40 ـ 55 سنة الممارسين وغير الممارسين للأنشطة الترويحية الرياضية، وكانت أهم النتائج توجد فروق ذات دلالة إحصائية عند مستوى الدلالة(0.05≥α) لدى متقاعدي الجيش الوطني الشعبي سن 40 ـ 55 سنة الممارسين وغير الممارسين للأنشطة الترويحية الرياضية. وقد تمت الاستعانة بالوسائل الإحصائية التالية : - المتوسطات الحسابية . - اختبار مان وتني (u) لعينتين مستقلتين و اختبار (ت) تستيودنت لعينتين مستقلتين. اختبار ليفين (levene) لحساب التجانس .معامل الارتباط بيرسون . وقد تمت المعالجة الإحصائية باستخدام برنامج الحزم الإحصائية للعلوم الاجتماعية (SPSS25) // // // // // // Abstract Study title: The effectiveness of practicing recreational sports activity in achieving mental health among People’s National Army retirees 40-55 years old The current study aimed to determine the effectiveness of practicing recreational sports activity in achieving psychological health among People’s National Army retirees aged 40-55 years. We used a sample of 50 professors divided into two groups, one of which was 25 retirees practicing recreational sports activities, and the second sample was 25 retired professors who did not practice any sports activity. The descriptive approach was used, using the psychological health scale. Accordingly, the student assumed that People’s National Army retirees aged 40-55 years who practice recreational and sports activities are characterized by a high level of mental health compared to their peers who do not practice recreational sports activities with an average level of mental health. The second hypothesis: There are statistically significant differences at the significance level (0.05≥α). Among People's National Army retirees aged 40-55 years who practice and do not practice recreational sports activities, the most important results were that there were statistically significant differences at the significance level (0.05≥α) among People's National Army retirees aged 40-55 years who practice and do not practice recreational sports activities. The following statistical methods were used: - Arithmetic averages. - Mann-Whitney U-test for two independent samples and Student's t-test for two independent samples. Levene test to calculate homogeneity. Pearson correlation coefficient. Statistical processing was done using the Statistical Package for the Social Sciences (SPSS25) program.
MEPS-2024-39
Keywords: النشاط الرياضي الترويحي - الصحة النفسية - متقاعدي الجيش الوطني الشعبي // // : recreational sports activity- mental health - People's National Army retirees